2012
DOI: 10.1111/j.1537-2995.2012.03632.x
|View full text |Cite
|
Sign up to set email alerts
|

How do we teach pediatric topics in transfusion medicine: curriculum development, learners, and instructional strategies

Abstract: ABBREVIATIONS: Ped TM = pediatric transfusion medicine; PTMAA = Pediatric Transfusion Medicine Academic Awardees; TM = transfusion medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Cascade learning through the dissemination of best practice by transfusion champions from different disciplines, however, has been effective in changing the culture of transfusion practice (Oliver et al , ), and this concept was by introduced by several groups during the research. It was felt that transfusion champions would be supportive, rather than hands‐on, providers of formal education as students require time away from work to learn (Ambruso et al , ), as we were able to confirm.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Cascade learning through the dissemination of best practice by transfusion champions from different disciplines, however, has been effective in changing the culture of transfusion practice (Oliver et al , ), and this concept was by introduced by several groups during the research. It was felt that transfusion champions would be supportive, rather than hands‐on, providers of formal education as students require time away from work to learn (Ambruso et al , ), as we were able to confirm.…”
Section: Discussionsupporting
confidence: 54%
“…Individual hospitals continue to develop induction e‐learning modules, including those aimed at transfusion practice. The authors, however, caution users about the over‐reliance on this method, which we agree must be incorporated into other methods of transfusion education delivery (Ambruso et al , ; Cottrell & Donaldson, , Hibbs, ).…”
Section: Discussionmentioning
confidence: 91%
“…This concerning finding should be interpreted alongside the observation that nearly all of the participants in this exam are consenting patients for, and managing the transfusion of, blood products. As pediatric transfusion medicine provides its own challenges and topics to consider, 17‐19 our study highlights the pressing need for further resources and initiatives to be aimed at pediatric‐specific transfusion medicine education. Pediatric residents recognize the importance of transfusion medicine education, with over 70% indicating that additional training in this area would be very or extremely helpful.…”
Section: Discussionmentioning
confidence: 98%
“…Further, pediatric patients have been noted to experience an increase in transfusion reactions compared to adult patients 15,16 . The existence of pediatric specific guidelines emphasize the fact that there are differences in transfusion needs for this population 17‐19 . These unique aspects of pediatric transfusion medicine highlight the need for pediatric focused transfusion medicine assessments and educational programs, but prior knowledge assessment studies have primarily been reported for specialty caring only for adult patients 6‐10 …”
Section: Introductionmentioning
confidence: 99%
“…Types of objectives include knowledge, affective and performance‐based. Traditionally, TM education has been focused on knowledge objectives such as in the TMAA curriculum and paediatric TM curriculum , or have been comprehensive in identifying the various clinical competencies needed in TM for pathology residents or TM fellows . While comprehensive, these lists may be overwhelming, particularly for the non‐TM physician, and challenging to incorporate into curricula where TM is but one of many educational topics.…”
Section: Step 3: Goals and Objectivesmentioning
confidence: 99%